Influence of body mass index on clinical outcomes in venous thromboembolism: Insights from GARFIELD‐VTE - Weitz, Jeffrey I.; Farjat, Alfredo E.; Ageno, Walter; Turpie, Alexander G. G.; Haas, Sylvia; Goto, Shinya; Goldhaber, Samuel Z.; Angchaisuksiri, Pantep; Gibbs, Harry; MacCallum, Peter; Carrier, Marc; Kayani, Gloria; et al. (Journal of thrombosis and haemostasis, 2021)
Background There is limited information on the influence of body mass index (BMI) on clinical outcomes in patients with venous thromboembolism (VTE). Objectives Investigate the influence of BMI on baseline characteristics, treatment patterns, and 24‐month outcomes in VTE patients. Methods GARFIELD‐VTE is a prospective, non‐interventional study of 10 869 patients with objectively confirmed VTE. Patients were grouped according to BMI: <18.5 (underweight; n = 214); 18.5–24.9 (normal; n = 2866); 25.0–29.9 (overweight; n = 3326); ≥30 (obese; n = 3073). Results Compared with patients with a normal BMI, obese patients were more frequently Caucasian (77.4% vs. 57.9%), treated in the outpatient setting (30.4% vs. 23.1%), and had previous VTE (17.5% vs. 11.7%). Active cancer was associated with lower BMI (underweight: 30.4%, normal: 13.5%, overweight: 9.4%, obese: 7.0%). At baseline, overweight and obese patients less often received parenteral therapy alone (16.7% and 14.4%) compared with those with an underweight or normal BMI (30.8% and 21.6%). Obese patients more commonly remained on anticoagulants for ≥2‐years compared to those with a normal BMI (52.3% vs. 37.7%). After 24‐months, the risk of all‐cause mortality was lower in overweight and obese patients than in those with normal BMI (adjusted hazard ratio [95% CI]; 0.75 [0.63–0.89] and 0.59 [0.49–0.72], respectively). Underweight patients more often experienced major bleeding (2.45 [1.41–4.26]) and all‐cause mortality (1.90 [1.43–2.53]) than patients with a normal BMI. Recurrent VTE was comparable among groups. Conclusion Underweight VTE patients have the highest risk of mortality and major bleeding. The risk of mortality in obese VTE patients is lower than that in VTE patients with a normal BMI.